(untitled) (Asian Education Studies, 2023)
The purpose of this study is to explore the views of teachers regarding their evaluation and professional development. The preferred methodology is a qualitative approach which has used the semi-structured interview as a data collection technique on a sample of ten primary school teachers. The respondents considered as the main purpose of their evaluation the improvement which results from the interlinkage between the identification of weaknesses and the implementation of training interventions. As far as the evaluation criteria are concerned, they mainly highlighted the teacher’s professional skills, the learning environment and the consistency of service. Persons close to the teacher, such as the director, colleagues, the teachers themselves and the Education Advisοr are considered to be the most appropriate actors. The benefits of the evaluation include the rewarding of the teachers and the recognition of their work, as well as the establishment of a culture of evaluation, while the disadvantages include negative emotions and unfair practices (e.g., stress, fear, pressure, insecurity, competition), negative consequences (e.g., salary reduction, dismissal), categorization of teachers and additional workload. Professional development is regarded as extremely useful and necessary and is achieved through formal, non-formal or informal processes. Finally, the respondents considered that the teachers‟ evaluation is directly linked to their professional development, as the former feeds the latter.